Strength and conditioning for football - Walker, G. J. (Strength and conditioning for sports performance, 2016)
The role of strength and conditioning (S&C) in the athletic development of football players is twofold: 1) reduce the likelihood of injury occurrence; and 2) improve physical performance. These dual roles are clearly inter-related. If players remain injury free, they have sufficient training opportunity to improve their performance, from a physical and tactical and technical perspective. This opportunity to increase their physical prowess should reduce the likelihood of future injury occurrence and promote a positive athletic performance cycle. The extensive nature of the football annual calendar presents a number of challenges to the S&C practitioner in terms of planning and subsequent periodisation of fitness parameters throughout a competitive season. Professional male players of Europe`s elite teams participate in over 200 training sessions and up to 60 competitive matches per season, with extensive national and international travel commitments [1J. Seasonal variations in fixture scheduling expose the players to a potential low of matches played every 3.3 days over a five-match time period. Conditioning programmes therefore must be carefully planned, based upon a thorough needs analysis of the sport and athlete, and delivered in accordance with the athlete and sports coach goals, together with the demanding fixture schedule.